INSTYTUCJA WYMIARU UZUPEŁNIAJĄCEGO W ORDYNACJI PODATKOWEJ - Rotkiewicz, Agnieszka (Civitas et Lex, 2016)
This article analyses and presents the complementary assessment in a tax proceeding regulated in the art. 230 the Act of 29 August 1997. The established solution raised great interest in literature and judicial decisions of the administrative courts. The legislator decided that the administrativereview authority was obliged to remand the case to the first-instance tax authority in order to amend the issued administrative decision if the tax liability or a taxable base was determined or specified in an amount lower than that proceeding from provisions on tax law. The first-instance tax authority issued a new administrative decision in accordance with the legal state in force on the day tax liability arose. The author notices that the mentioned regulation made the legal position of parties worse, due to the fact that the first-instance authority could have issued a new administrative decision detrimental to the party petitioning for review. However it must be noted that the institution of the complementary assessment was revoked in 2013. It means that the party’s situation can’t be worsened unless the appealed administrative decision grossly breaches law or the public interest.